Subsurface aeration mitigates organic material mulching-induced anaerobic stress via regulating hormone signaling in Phyllostachys praecox roots - Gao, Jianshuang; Zhuang, Shunyao; Gui, Renyi (Frontiers in Plant Science, 2023)
Organic material mulching has been used extensively to allow Phyllostachys praecox to promote growth and development of shoots. However, the bamboo forest always showed a significant degradation, probably due to anaerobic damage caused by the mulching after several years. Therefore, we have innovatively proposed an improvement measure to aerate the underground pipes for the first time. We investigated the role of subsurface pipe aeration in regulating root hypoxia to reduce the stress and to identify the degradation mechanism. Results showed that aeration increased oxygen concentration, shoot yield and root growth compared with mulching, and the aeration enhanced the concentration of indole-3-acetic acid (IAA) and the expression of Aux/IAAs (Aux1, Aux2, Aux3, and Aux4). Aeration reduced gibberellin (GA), ethylene (ETH), and abscisic acid (ABA) contents as well as anaerobic enzyme activities (alanine transaminase, AlaAT; alcohol dehydrogenase, ADH; pyruvate decarboxylase, PDC; and lactate dehydrogenase, LDH), which alleviated root damage in anoxic conditions. Furthermore, correlation showed that the activities of ADH, LDH, PDC, and AlaAT showed significant linear correlations with soil oxygen levels. RDA analyses showed that ABA, IAA, and ETH were found as the key driving hormones of Aux/IAAs in the root of the forest mulched with organic material. Here we show that subsurface aeration increases soil oxygen concentration, shoot yield, root growth and regulates phytohormone concentrations and Aux/IAAs expression, which reduces anaerobic enzyme activities. Consequently, subsurface pipe aeration is an effective measure to mitigate the degradation of bamboo forests caused by soil hypoxia that results from organic material mulching.